ONLINE LEARNING EFFECTIVENESS: THROUGH DIGITAL LITERACY AND TEACHER’S PROFESSIONAL COMPETENCE - Lu’luul Mukaromah; Cipto Wardoyo (Universitas PGRI Madiun, 2022)
ABSTRACTThis study aims to measure and analyze the effect of digital literacy and teachers' professional competence on the effectiveness of online learning. This research is quantitative research with a quantitative explanatory approach using a questionnaire. The research sample was 190 students of 11th-grade Financial Accounting using the purposive sampling technique. The data analysis used is multiple linear regression. The results showed that (1) digital literacy had a positive effect on the effectiveness of online learning, and (2) teachers' professional competence had a positive effect on the effectiveness of online learning. Teachers can use the findings in this study to increase the effectiveness of online learning. Teachers must master the material of learning and utilize technology to provide interactive online learning. Interactive online learning will help students improve problem-solving skills, critical thinking abilities, and adaptability. ABSTRAKPenelitian ini bertujuan untuk mengukur dan menganalisis pengaruh literasi digital dan kompetensi profesional guru terhadap efektivitas pembelajaran daring. Penelitian ini penelitian kuantitatif dengan pendekatan eksplanatif menggunakan kuesioner. Pengambilan sampel menggunakan teknik purposive sampling sejumlah 190 siswa kelas XI Akuntansi Keuangan dan Lembaga. Analisis data yang digunakan adalah regresi linier berganda. Hasil penelitian menunjukkan bahwa (1) literasi digital berpengaruh positif terhadap efektivitas pembelajaran daring, dan (2) kompetensi profesional guru berpengaruh positif terhadap efektivitas pembelajaran daring. Temuan dalam penelitian ini dapat digunakan oleh guru dalam upaya meningkatkan efektivitas pembelajaran daring dimana guru harus mampu menguasai materi secara menyeluruh dan memanfaatkan teknologi untuk menyediakan pembelajaran daring yang nyaman dan interaktif. Pembelajaran daring yang interaktif akan membantu siswa memiliki keterampilan pemecahan masalah, kemampuan berpikir kritis, dan kemampuan beradaptasi di kalangan siswa.